Analisis Peran Komunikasi Aktor Pemerintah dan Non Pemerintah Memerangi Misinformasi Vaksinasi Covid-19 di Indonesia - Hasanah, Fatimah Nur (Jurnal Administrasi dan Kebijakan Publik, 2023)
Misinformation has become a barrier to public trust in a policy, especially during the Covid-19 pandemic crisis. The role of communication between government and non-government actors is indispensable in implementing policies and combating Covid-19 vaccination misinformation on social media. This study aims to understand the roles and communication strategies of government and non-government actors in combating misinformation about the Covid-19 vaccination policy in Indonesia. This paper used the content analysis research method. Data were collected from tweets from 1 January to 31 December 2021. The results show the role of communication between government and non-government actors through the guiding principles of crisis communication such as calls to action, clarity, compassion and empathy, tone of dialogue, correction of misinformation, and transparency. This research used information communication technologies (ICTs), public involvement, response, collaboration, and utilization of the Situational Crisis Communication Theory (SCCT) strategy. Finally, a collaboration between actors in various sectors will strengthen policy communication in eradicating misinformation. This study contributed to relevant literature and has practical implications for sustainable policy communication in times of crisis.